Macrophage Migration Inhibitory Factor Interacting with Th17 Cells May Be Involved in the Pathogenesis of Autoimmune Damage in Hashimoto’s Thyroiditis - Haibo Xue; Yuhua Yang; Ying Zhang; Shoujun Song; Li Zhang; Lei Ma; Tingting Yang; Huan Liu (Mediators of Inflammation)
Purpose. To explore the possible role of MIF and Th17 cells in the thyroid-specific autoimmune damage of Hashimoto’s thyroiditis (HT). Material and Methods. We enrolled 40 HT patients and 30 healthy controls and divided HT patients into euthyroid subset (n=22) and subclinical or overt hypothyroidism subset (n=18). The percentages of Th17 cells and expressions of MIF, interleukin 17A (IL-17A) mRNA in PBMCs, as well as serum concentrations of MIF, and IL-17A, and thyroid functions, and thyroid-specific autoantibodies (TPOAb, TgAb) were detected by flow cytometry, real-time RT-PCR, ELISA, and ECLIA in all subjects. Results. MIF mRNA, IL-17A mRNA expressions and Th17 cells percentages, serum MIF, and IL-17A protein levels were all significantly higher in HT patients, even in euthyroid subgroup. Additionally, the differences became more obvious in dysfunction subgroup. Importantly, both MIF levels and Th17 cells percentage were positively correlated with serum TPOAb, TgAb, and thyrotropin (TSH) levels in HT patients. Conclusions. These data suggest that MIF and Th17 cells increased dynamically and positively correlated with the markers of thyroid autoimmune damage, which indicated that interaction between MIF and Th17 cells may participate in the pathogenesis and development of thyroid-specific autoimmunity in HT.